A class of dynamic contact problems with Coulomb friction in viscoelasticity. (April 2015) - Cocou, Marius
Abstract: The aim of this work is to study a class of nonsmooth dynamic contact problems which model several surface interactions, including relaxed unilateral contact conditions, adhesion and Coulomb friction laws, between two viscoelastic bodies of Kelvin–Voigt type. An abstract formulation which generalizes these problems is considered and the existence of a solution is proved by using Ky Fan's fixed point theorem, suitable approximation properties, several estimates and compactness arguments.